SUPERVISION BY THE SAMARINDA TRANSPORTATION AGENCY AND TRAFFIC POLICE UNIT IN RESTRICTING VEHICLES CROSSING THE ACHMAD AMINS BRIDGE IN SAMARINDA - Muhammad Jais Sullah Ramadhan; Hariati Hariati (Jurnal Aktor, 2026)
Traffic supervision on bridge infrastructure plays a crucial role in maintaining the security, safety, and sustainability of the bridge’s function as a public transportation facility. The increasing number of vehicles, particularly heavy-tonnage vehicles, can impose excessive loads that may damage the bridge structure. Therefore, the Samarinda City Government implements vehicle restriction policies on the Achmad Amins Bridge through supervision conducted by the Samarinda City Transportation Agency in collaboration with the Traffic Police Unit of Polresta Samarinda. This study aims to describe the supervision of vehicle restrictions on the Achmad Amins Bridge in Samarinda and to identify factors that hinder the effectiveness of such supervision. The research employed a qualitative descriptive approach with a case study design, collecting data through direct observation and in-depth interviews with officials from the Transportation Agency and Satlantas of Samarinda. Data analysis followed the interactive model developed by Miles, Huberman, and Sadana, comprising four components: data collection, data condensation, data presentation, and conclusion drawing. The results indicate that the Transportation Agency and Satlantas of Samarinda have conducted supervision of vehicle restrictions on the Achmad Amins Bridge; however, it is not yet optimal, as reflected in the indicators outlined in Samarinda Mayor Regulation No. 50 of 2023, namely: (a) monitoring and (b) inspection. The supervision is constrained by limited personnel and insufficient public awareness, resulting in drivers violating regulations by bypassing or crashing through restriction barriers, which can potentially cause traffic congestion or accidents.